SIX SITUATIONS PROVERBIAL METAPHOR THEORY - Almeida Panzo, André (Proverbium - Yearbook, 2017)
Peter Seitel formulated the three situations theory. On doing it, he misconceived proverbial metametaphor by proverbial metaphor, therefore misconceiving where to locate proverbial metaphor, locating it after the proverb situation, while it has got to be located before the proverb situation. Furthermore, the theory contains a gap on missing to draw basis on the proverb’s precedent as said Alan Dundes or the proverb’s philosophy as said Aristotle. Fixing these gaps, we propose a new theory, we label as the Six Situations Proverbial Metaphor Theory.